2015
DOI: 10.1097/nmd.0000000000000368
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Regional Homogeneity in Patients With Acute Mild Traumatic Brain Injury

Abstract: Mild traumatic brain injury (mTBI) is characterized by structural disconnection and large-scale neural network dysfunction in the resting state. However, little is known concerning the intrinsic changes in local spontaneous brain activity in patients with mTBI. The aim of the current study was to assess regional synchronization in acute mTBI patients. Fifteen acute mTBI patients and 15 sex-, age-, and education-matched healthy controls (HCs) were studied. We used the regional homogeneity (ReHo) method to map l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 54 publications
3
28
0
Order By: Relevance
“…Unlike the more traditional method of spectral coherence, PLS separates the phase and amplitude components and can be directly interpreted in the framework of neural integration. 80 In the present study, the frequency increments used in the Morlet wavelet transformation were at 0.5 Hz for the low-frequency band (1-7 Hz) and alpha band (8-12 Hz), at 1 Hz for the beta band (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and at 2 Hz for the gamma band . Similar to the Xcorr approach, ROIglobal FC measures were obtained using the PLS approach as the ROI-global connectivity vector with 94 elements.…”
Section: Roi-global Fc Using Roi Source Time Coursesmentioning
confidence: 75%
See 3 more Smart Citations
“…Unlike the more traditional method of spectral coherence, PLS separates the phase and amplitude components and can be directly interpreted in the framework of neural integration. 80 In the present study, the frequency increments used in the Morlet wavelet transformation were at 0.5 Hz for the low-frequency band (1-7 Hz) and alpha band (8-12 Hz), at 1 Hz for the beta band (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and at 2 Hz for the gamma band . Similar to the Xcorr approach, ROIglobal FC measures were obtained using the PLS approach as the ROI-global connectivity vector with 94 elements.…”
Section: Roi-global Fc Using Roi Source Time Coursesmentioning
confidence: 75%
“…In contrast, activity in the beta band (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) is associated with communication among remote brain structures, whereas gamma band (30-80 Hz) synchrony promotes local computations. 88,89 Probably because of its role in long-range communication, most of the rs-MEG FC studies have focused on the beta band.…”
Section: Differences Across Frequency Bands In Abnormal Fcmentioning
confidence: 95%
See 2 more Smart Citations
“…The ReHo abnormalities are a potential biomarker for the diagnosis of Parkinson’s disease, and they provide insights into the biological mechanism of the disease [28]. Zhan et al experimentally demonstrated that ReHo may provide an objective biomarker for evaluating the functional abnormity of mild traumatic brain injury under acute settings [29]. Liu et al proposed that ReHo is a potential neuroimaging biomarker for distinguishing bipolar disorder patients experiencing a depressive episode and unipolar depression patients [30].…”
Section: Discussionmentioning
confidence: 99%